DIAZOXIDE-INDUCED HYPERGLYCAEMIC CRISIS IN AN ELDERLY: A TRAP FOR THE UNWARY - Nazlee, Asma Mohd; Chan, Pei Lin; Tan, Florence Hui Sieng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Diazoxide inhibits pancreatic insulin secretion and is a well-established pharmacological agent for management of hypoglycaemia in insulinoma. Hyperglycemic emergencies associated with its use are rare, being mostly reported in the elderly and in children. CASE An 88-year-old female with hypertension and dyslipidaemia presented to the emergency room with syncope and was noted to be hypoglycaemic with capillary glucose of 2.6 mmol/L. She reported a year-long history of recurrent presyncopal episodes and early morning hunger pangs. Renal profile, 8 am cortisol, thyroid and liver function tests were normal. Laboratory tests confirmed endogenous hyperinsulinemia (random blood glucose: 1.7 mmol/L, serum insulin 373 pmol/L, C-peptide 3054 pmol/L) with negative sulfonylurea screening. CT imaging revealed a 0.4 × 0.9 cm hypodense lesion in the proximal pancreas. She was started on diazoxide and was advised glucose monitoring and dietary modifications. Her capillary blood glucose remained stable (5–7 mmol/L) on follow-up. However, weeks later, she presented again with reduced responsiveness. Investigations revealed overlapping diabetic ketoacidosis and hyperosmolar hyperglycaemic state with acute kidney injury (glucose 32 mmol/L, ketones 7.5 mmol/L, pH 7.2, HCO₃ 15 mmol/L, Na 162 mmol/L, urea 27 mmol/L, creatinine 309 µmol/L, osmolality 362 mOsm/L). CXR showed right lower zone consolidation. She was treated with antibiotics and insulin, requiring up to 30 units per day when steroid was added for bronchospasm. After recovery and weaning of steroids, insulin was tapered off. However, she experienced further episodes of hypoglycaemia despite being off all glucose-lowering medication. Diazoxide was resumed at 100 mg every other day. Family opted for non-surgical management and she remained well with normal home glucose profile on follow-up 3 months later. CONCLUSION This case highlights the rare but potentially life-threatening side-effect of diazoxide. The risk is heightened in the elderly, especially when confounded by renal impairment, high doses, intercurrent illness or steroid use. Awareness and vigilant monitoring are essential in the vulnerable to avoid adverse outcome.